Edukasi Pencegahan Penularan Covid-19 Guna Membentuk Karakter Anak Yang Sadar Kebersihan Sesuai Dengan Ajaran Islam Di RT.04/RW.02 Dusun Jatisari Desa Krenceng Kecamatan Kepung Kabupaten Kediri - Nailatul Muna; Siti Kalimah (LP3M IAIFA Kediri, 2021)
Education related to preventing the transmission of Covid-19 in the community, especially to children, is still very minimal and efforts are needed to make people aware of the importance of preventing Covid-19 through 5 M. Based on this context, this educational program is implemented to shape the character of children who are aware of cleanliness from an early age. This educational outreach program is considered quite successful in making children aware of the current environmental conditions. In this educational program, there is good cooperation and communication between researchers and the community as well as the participation of children in RT.04/RW.02 Jatisari, Krenceng Village, who are actively involved in the success of the program. The willingness of children to participate in this educational program to prevent the spread of Covid-19 also shows the success of this program. All the children practice one by one related to the procedures for wearing and removing masks, and how to wash hands using soap and running water or hand sanitizer in accordance with the health protocols recommended by the government. The success of this program can also be used as a model for implementing Covid-19 Transmission Prevention Education in other places by adjusting the existing context.